(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Background: The Kyrgyz Republic, with its high-altitude regions, poses unique health challenges due to extreme geoclimatic factors. Cardiovascular disease (CVD) is prevalent in the region, and dyslipidemia, a significant risk factor for atherosclerosis and CVD, is associated with elevated serum cholesterol levels. This study investigates the effects of high-altitude environments on human health and the potential therapeutic benefits of L-arginine in regulating carbohydrate and lipid metabolism. Materials and Methods: Thirty rabbits were divided into five groups: Control (low-altitude), high-altitude (3 days), atherosclerosis model, atherosclerosis with preventive L-arginine and cholesterol treatment, and atherosclerosis with L-arginine treatment. Atherosclerosis was induced by oral cholesterol administration (500 mg/kg/day) for 60 days. L-arginine (170 mg/kg/day) was administered for 30 days for treatment and prevention. Lipid metabolism indicators (high-density lipoprotein, low-density lipoproteins, triglycerides, and total cholesterol [TC]) were measured using a biochemical autoanalyzer. Histological examination of excised plaques and myocardial morphology was performed. Results: Results showed a significant reduction in TC levels in the high-altitude group compared to the control. The atherosclerosis model group exhibited a tenfold increase in TC, which remained unchanged with preventive L-arginine and cholesterol treatment. However, L-arginine treatment alone decreased TC levels by approximately 65%, although still twice as high as the control. Conclusion: The findings suggest that L-arginine may have potential therapeutic benefits in regulating lipid metabolism and improving cardiomyocyte morphology in rabbits with induced atherosclerosis under high-altitude conditions.